An unusual tumulus or cenotaph at Cozzo Rotondo, town of Grifone (Bisignano, Cosenza, Italy). New and old geological investigation for an archaeological discovery - Vincenzo Rizzo; Mario Panizza (Groma)
The hillock named “Cozzo Rotondo”, in Grifone (Bisignano, province of Cosenza, Italy), has attracted the attention of numerous researchers since 1986, when it was discovered, and – owing to its peculiar morphology – is described as a monumental tumulus. This research, integrating old unpublished data and new ones, aims to define its internal structure and how it was made. In fact , its shape is in striking contrast with the geomorphological context of the surrounding area. Its shape, orientation and spatial setting recall many tumuli of Central Europe. A series of popular myths and legends, as well as its curious name, are associated with this hillock, conferring it a certain halo of mystery. The geological, geophysical and geomorphological investigations carried out in the past – in particular those quoted in this study – confirm that this hillock is made up of homogeneous sand arranged in natural layers and that its shape is the result of the digging and remodelling of a natural slope. Based on geomorphological observations, it has been estimated that the volume of earth dug out is about 8,000 m3, concentrated nearly exclusively in the southwestern sector of the hillock, where the soils are more recent and thinner. Subsequently, the material was scattered in the underlying plain, thus forming a gentle bluff, some 1-2 m thick, over an area of 4,000 m2, as confirmed by georadar surveying. In particular, geological investigations carried out on a series of excavations have clearly shown the presence of a moat surrounding an ancient building and a clayey colluvium, which were dated to the 8th century CE (by means of 14C dating) and after the 8th century BCE (by means of fluorescence analyses), respectively. It was therefore suggested that the digging and remodelling activities took place in this time interval. Geoelectrical and georadar surveying seems to show the absence of voluminous finds, strengthening the hypothesis – expressed also by many archaeologists – that the hillock of Cozzo Rotondo is a quaint tumulus resulting from accurate partial modelling, almost totally made by a sort of “deep carving”. More likely, it is a monumental cenotaph, built in a very original way.